Site-specific glycosylation of the human cytomegalovirus tegument basic phosphoprotein (UL32) at serine 921 and serine 952. - Greis, K D (1994)
The virion basic phosphoprotein (BPP), UL32, of the human cytomegalovirus (HCMV) is a 149-kDa tegument protein that represents about 15% of the virion protein mass and is modified by O-linked N-acetylglucosamine (O-GlcNAc). O-GlcNAc has been postulated to mediate subunit-subunit interaction in many different types of intracellular protein complexes, while BPP may play a role in viral assembly and/or envelopment. This report describes the identification of the major O-GlcNAc attachment sites on the HCMV (AD169) BPP. Because the amount of BPP isolated from infectious virions was insufficient to determine the site(s) of glycosylation, the full-length protein has been characterized following overexpression in recombinant baculovirus-infected insect cells. The recombinant protein (rBPP) was electrophoretically (by sodium dodecyl sulfate-polyacrylamide gel electrophoresis) and immunologically (by Western immunoassaying) indistinguishable from the BPP isolated from HCMV virions. In addition, the rBPP was modified by O-GlcNAc, and a comparison of the tryptic glycopeptides from the rBPP and native virion BPP indicated that their O-GlcNAc sites are the same. Furthermore, the major sites of O-GlcNAc attachment to the rBPP were mapped on high-performance liquid chromatography-purified glycopeptides by gas phase microsequencing, manual Edman degradation, and electrospray-mass spectrometry. The results demonstrate that the major sites of O-GlcNAc attachment to the BPP are Ser-921 and Ser-952. Identification of these sites will now enable mutagenesis studies to determine the influence of O-GlcNAc on the intracellular location, protein-protein interaction, and biological function of BPP. Finally, the fidelity of the addition of O-GlcNAc to rBPP in insect cells compared with native virion BPP is documented to demonstrate the possible general applicability of the baculovirus expression system to study O-GlcNAc on other low-abundance proteins.